Regulatory and Ethical Aspects of Orthobiologic Therapies. Issue 11 (25th November 2022) - Murray, Iain R.; Chahla, Jorge; Wordie, Sarah J.; Shapiro, Shane A.; Piuzzi, Nicolas S.; Frank, Rachel M.; Halbrecht, Joanne; Okada, Kiyoshi; Nakamura, Norimasa; Mandelbaum, Bert; Dragoo, Jason L.; ,; et al.
Orthobiologic therapies show significant promise to improve outcomes for patients with musculoskeletal pathology. There are considerable research efforts to develop strategies that seek to modulate the biological environment to promote tissue regeneration and healing and/or provide symptomatic relief. However, the regulatory pathways overseeing the clinical translation of these therapies are complex, with considerable worldwide variation. The introduction of novel biologic treatments into clinical practice raises several ethical dilemmas. In this review, we describe the process for seeking approval for biologic therapies in the United States, Europe, and Japan. We highlight a number of ethical issues raised by the clinical translation of these treatments, including the design of clinical trials, monitoring outcomes, biobanking, "off-label" use, engagement with the public, marketing of unproven therapies, and scientific integrity.